2012
DOI: 10.7243/2049-7962-1-30
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene enhances the anti-proliferative and pro-apoptotic effects of capsaicin in prostate cancer in vitro

Abstract: Background: Increasing evidence suggests dietary factors influence the development and progression of prostate cancer (PCa). The chemopreventive properties of lycopene, the antioxidant found in tomatoes, have been extensively studied for PCa; however, the effect of lycopene, as a single agent, remains unclear. Studies that are more promising, involve using lycopene in combination with other dietary agents. Capsaicin, the active compound in chilli peppers, is reported to exert potent anti-cancer effects in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Unfortunately, these concentrations are still 10‐100‐fold higher than our in vitro analysis that has been reported. However, it is still unclear whether capsaicin can accumulate in certain tissues (i.e., prostate tissue), as reported with other dietary agents (e.g., lycopene) . It is also possible that the metabolite glucuronide that we identified may possess anti‐cancer properties.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Unfortunately, these concentrations are still 10‐100‐fold higher than our in vitro analysis that has been reported. However, it is still unclear whether capsaicin can accumulate in certain tissues (i.e., prostate tissue), as reported with other dietary agents (e.g., lycopene) . It is also possible that the metabolite glucuronide that we identified may possess anti‐cancer properties.…”
Section: Discussionmentioning
confidence: 75%
“…The apoptotic effect of capsaicin on cancer cells has been more consistently documented in the recent literature across various cancer sites, including the prostate . The majority of these studies have reported that capsaicin acts predominately by inducing intrinsic apoptosis through the generation of reactive oxygen species (ROS), disruption of the mitochondrial membrane, alterations in bax to bcl‐2 ratio and subsequent release of cytochrome C, and by the activation of the caspase–cascade .…”
Section: Introductionmentioning
confidence: 99%
“…Although the abovementioned physiological processes are associated with increased cell viability and mitogenic processes, there are only few studies reporting that CAPS increase cell proliferation of cancer cells. While CAPS (50 μM) increases the proportion of cells present in the G 2 phase, the proportion of G 0 /G 1 cells is decreased compared to control (untreated) LNCaP cells [52]. Similarly Malagarie-Cazenave et al…”
Section: Discussionmentioning
confidence: 79%
“…Western Blot analyses of lysates from PC3 treated cells were carried out as described. 10 Briefly, PC3 cells were plated at a density of 1 × 10 6 cells per 10 cm plate. Twenty-four hours after plating, adherent cells were treated with WIN (10-20 μM).…”
Section: Western Blot Analysismentioning
confidence: 99%